Comprehensive knowledge about HIV/AIDS and associated factors among reproductive age women in Liberia - Beminate Lemma Seifu; Gilbert Eshun; Getayeneh Antehunegn Tesema; Frank Kyei-Arthur (BMC, 2024)
Abstract Introduction Acquired Immune Deficiency Syndrome (AIDS) continues to be a deadly pandemic and a serious threat to public health. Globally, reproductive age women are more likely to be infected with Human Immunodeficiency Virus (HIV). Comprehensive knowledge about HIV/AIDS is pivotal in the fight against AIDS. However, comprehensive HIV/AIDS knowledge is low in Sub-Saharan African (SSA) nations including Liberia, which contributes to the high incidence of HIV in these nations. This study assessed the level of comprehensive knowledge about HIV/AIDS and its associated factors among reproductive age women in Liberia. Methods The prevalence and associated factors of comprehensive knowledge about HIV/AIDS among reproductive age women in Liberia were determined using secondary data analysis of 2019-2020 Liberia Demographic and Health Surveys (LDHS). Comprehensive knowledge about HIV/AIDS was a composite variable computed from six variables available in the Demographic and Health Survey (DHS). The study included 7,621 reproductive age women in weighted samples. A generalized linear mixed model with robust error variance was used. For the variables included in the final model, adjusted prevalence ratios (aPR) with 95% confidence intervals (CI) were calculated. Results The prevalence of comprehensive HIV/AIDS knowledge among Liberian women aged 15-49 was 33.5%. Women's age and education, and distance to health facility were positively associated with comprehensive knowledge about HIV/AIDS among Liberian reproductive age women. In contrast, community poverty level was negatively associated with comprehensive knowledge about HIV/AIDS. Conclusion and recommendations This study demonstrates that the prevalence of good comprehensive HIV/AIDS knowledge was relatively low among reproductive age women in Liberia. Hence, health practitioners and policymakers should strengthen HIV/AIDS sensitization programmes to increase women's knowledge about HIV/AIDS.